Improving the Quality of Indihome Complaints Service Using Lean Service Method (Case Study of Customer Care Plasa Telkom Solo) - Eko Pujiyanto; Fakhrina Fahma; Savitri Kusumaning Ayu (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
PT. Telkom Indonesia is a company engaged in the telecommunications sector. Nowadays, the necessity for internet networks has increased, notably since the COVID-19 pandemic. Thus, PT. Telkom Indonesia as the largest telecommunications company in Indonesia need to improve the quality of service, especially in the Indihome complaint service process. The Indihome service complaint process often causes many queues so that customers have to wait a long time to be served. This study uses the Lean Service method, by identifying 7 wastes in service companies and then reducing the amount of waste that occurs which causes inefficient and effective service processes. This study also uses VALSAT (Value Stream Analysis Tools) to identify waste in the service system flow. In the Indihome complaint service process, there are the most critical waste, namely the waste of delays and the waste of under-utilized resources. The proposed improvements for waste of delays and waste of under-utilized resources are maximizing the use of VIRSA (Virtual Plasa) machines, educating customers to use MyIndihome application, and conducting regular training for CSR employees. Through value stream mapping current state, it is known that the total time for customers to get service is 1709 seconds and through value stream mapping future state, it is known that the total time for customers to get service is 1468 seconds for each customer.